Bioglycerol (C3) upgrading to 2,3-butanediol (C4) by cell-free extracts of Enterobacter aerogenes NCIM 2695 - Parate, Roopa; Borgave, Mrunal; Dharne, Mahesh; Rode, Chandrashekhar (Journal of Chemical Technology and Biotechnology, 2021)
BACKGROUND Production of biobased chemicals from renewable resources is a green starring approach that serves as a substitute to petroleum derivatives. Bioglycerol, with its growing production as a co-product of biodiesel, is an attractive low-cost feedstock for the synthesis of platform chemicals by microbial fermentation. 2,3-butanediol (2,3-BDO) is amongst the top biorefinery platform chemicals that can be produced by glycerol fermentation. RESULTS The `Circular Economy' concept is demonstrated by converting the by-product bioglycerol using a cell-free extract of Enterobacter aerogenes NCIM 2695 (National Collection of Industrial Microorganisms, NCIM), yielding 22 g L-1 2,3-BDO, in 96 h, 98% atom economy and 0.4 g/g E factor. The cell-free bioglycerol conversion to 2,3-BDO was proved using a modified procedure for determining glycerol dehydrogenase enzyme assay by protein analysis and it was also shown to be cell-bounded. CONCLUSION Our study offers an effective utilization of the leftover material (i.e. cell-free extract) that biocatalysed C3 to C4 diol, which adds value to the overall economics of the process using only crude glycerol (C3) itself as a fermentative medium.
Keywords: 2; 3-Butanediol; atom economy; circular economy; E factor; Glycerol; glycerol dehydrogenase

Bacteriophages: status quo and emerging trends toward one health approach - Samson, Rachel; Dharne, Mahesh; Khairnar, Krishna (Science of The Total Environment, 2024)
The alarming rise in antimicrobial resistance (AMR) among the drug-resistant pathogens has been attributed to the ESKAPEE group (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumanii, Pseudomonas aeruginosa, Enterobacter sp., and Escherichia coli). Recently, these AMR microbes have become difficult to treat, as they have rendered the existing therapeutics ineffective. Thus, there is an urgent need for effective alternatives to lessen or eliminate the current infections and limit the spread of emerging diseases under the ``One Health'' framework. Bacteriophages (phages) are naturally occurring biological resources with extraordinary potential for biomedical, agriculture/food safety, environmental protection, and energy production. Specific unique properties of phages, such as their bactericidal activity, host specificity, potency, and biocompatibility, make them desirable candidates in therapeutics. The recent biotechnological advancement has broadened the repertoire of phage applications in nanoscience, material science, physical chemistry, and soft
Keywords: Antimicrobial resistance (AMR); Bacteriophages; One-health; Therapeutics commercialization